New Considerations for a Totally Implantable Active Middle Ear Implant - Shohet, Jack; Bibee, Jacqueline (Frontiers in Neurology, 2021)
Totally implantable active middle ear implants (AMEI) provide full-time hearing amplification to those with moderate to severe sensorineural hearing loss. While technology in conventional hearing aids (CHA) has advanced greatly, limitations remain for people with active lifestyles, limited vision or dexterity, and hearing aid fit issues. Furthermore, direct-drive properties of AMEI are thought to provide those with inefficient middle ear transfer functions a distinct advantage in delivering prescribed sound to the cochlea, ultimately improving speech understanding with less distortion. AMEI safety, stability, and efficacy outcomes are well documented and fitting strategies continue to improve. Recent studies show how simple aided speech testing can help predict whether a patient struggling with CHA may instead benefit from an AMEI. Totally implantable AMEI continue to be a viable option for patients who cannot or will not utilize traditional hearing aids.